Analysis of Synonymous Codon Usage Bias in Flaviviridae Virus. (27th June 2019) - Yao, Huipeng; Chen, Mengyu; Tang, Zizhong
Abstract : Background . Flaviviridae viruses are single-stranded, positive-sense RNA viruses, which threat human constantly mediated by mosquitoes, ticks, and sandflies. Considering the recent increase in the prevalence of the family virus and its risk potential, we investigated the codon usage pattern to understand its evolutionary processes and provide some useful data to develop the medications for most of Flaviviridae viruses. Results . The overall extent of codon usage bias in 65 Flaviviridae viruses is low with the average value of GC contents being 50.5% and the highest value being 55.9%; the lowest value is 40.2%. ENC values of Flaviviridae virus genes vary from 48.75 to 57.83 with a mean value of 55.56. U- and A-ended codons are preferred in the Flaviviridae virus. Correlation analysis shows that the positive correlation between ENC value and GC content at the third nucleotide positions was significant in this family virus. The result of analysis of ENC, neutrality plot analysis, and correlation analysis revealed that codon usage bias of all the viruses was affected mainly by natural selection. Meanwhile, according to correspondence analysis (CoA) based on RSCU and phylogenetic analysis, the Flaviviridae viruses mainly are made up of two groups, Group I (Yellow fever virus, Apoi virus, Tembusu virus, Dengue virus 1, and others) and Group II (West Nile virus lineage 2, Japanese encephalitis virus, Usutu virus, Kedougou virus, and others). Conclusions . All in, the bias of codon usage pattern is affected not only by compositional constraints but also by natural selection. Phylogenetic analysis also illustrates that codon usage bias of virus can serve as an effective means of evolutionary classification in Flaviviridae virus.